Protonation of apolar species: From Cl2H+ to (E)-NCCHCHCNH+ through computational investigations - Alessandrini, Silvia; Bizzocchi, Luca; Melosso, Mattia; Puzzarini, Cristina (Frontiers in Astronomy and Space Sciences, 2023)
Radioastronomy is a powerful tool for the discovery of molecules in space but it requires molecular species to be polar. The observation of apolar species can be however enabled by protonation, which occurs from reaction with the abundant H3+ ion whenever the proton affinity of the species under consideration is greater than that of H2. This property can be easily investigated by computational chemistry and, in this work, it has been used to asses the potential protonation of simple homo diatomics, such as Cl2, P2, and Si2, as well as apolar species containing two equivalent CN moieties, such as diisocyanogen (CNNC) and (E)-1,2-dicyanoethene. Quantum chemistry has also been exploited to investigate the mechanisms of three protonation reactions of H3+ with Cl2, P2, and CNNC. To support laboratory measurements and astronomical observations of the resulting transient species, their rotational spectroscopic parameters were accurately computed together with fundamental vibrational frequencies. For this purpose, we have employed CCSD(T)-based computational methodologies, which provide equilibrium structures with errors smaller than 0.001 Å and 0.1° for bond distances and angles, respectively. Such an accuracy is expected to lead to rotational constants predicted, in relative terms, with uncertainties better than 0.2%. Instead, the expected accuracy on vibrational frequencies is ∼10 cm−1, thus being well suited to guide band assignments.